Beneficence and non-maleficence: collaborative practice and harm mitigation. Issue 2 (2nd February 2022) - Bifarin, Oladayo; Stonehouse, David
Abstract : This article is the third in a series of three, discussing and applying four ethical principles as identified by Beauchamp and Childress (2019) . This final article examines the two interrelated principles of beneficence and non-maleficence. First, we will present definitions identifying the differences between the two. Then we will identify relevant and pertinent parts of the Nursing and Midwifery Council (NMC) (2018) code will be identified. This will be followed by a discussion on how beneficence and non-maleficence can be demonstrated and practised within the clinical environment to patients, their families, your colleagues, and yourself.